TEACHER LEARNING STRATEGIES TO IMPROVE THE QUALITY OF STUDENT LEARNING - Prasetyo, Gian Bagus (Universitas Pendidikan Indonesia, 2024)
This paper aims to describe the teacher's learning strategy in improving the quality of student learning at SMK Mardiwiata. The type of research in this paper is descriptive research and uses qualitative data. The results of this study are the achievement of active, innovative and creative learning thanks to the learning strategies used by teachers. Learning that is usually, with educators who are too monotonous in carrying out teaching and learning activities, is usually caused by ordinary teachers and only explaining the material. This is also because students will get bored quickly and finally students experience a decrease in interest in the subject. The learning strategies provided later include (1) having a desire; (2) fostering a sense of pleasure and interest; (3) having attention; (4) increasing self-awareness; and (5) concentration.